California Advocate Newspaper's Drum Major for Justice Dinner at Hilton Hotel - Watkins, Howard::::::::: (1988)
Ron McNair, Cynthia George McNair, Luisa Medina, Lindell Cross, Barbara Gaines, Sandra Iyall